Results of implementation of decision-problem based learning with virtual patients in surgery in the frames of tame: training against medical error project realization - Avramenko, М. О.; Furyk, O. O.; Pavlenko, A. S.; Авраменко, Микола Олександрович; Фурик, Олена Олександрівна; Павленко, Альона Сергіївна (My University, 2018)
The aim of the research is to specify the outcomes of the implementation of learning on Virtual Patients in Surgery within the TAME: Training Against Medical Errors Project.
Keywords: medical error; surgery; course